Легенда горного ручья: рассказы о привидениях : пер. с англ. / К. Кин - Кин К. (Детский детектив, 1995)
Экземпляры: ДО () / Инвентарный номер: 20398 / Цена: 4420.00 / Авт.знак: К 41 / ГРНТИ: 17 / ББК: 84(7Сое)